Negotiating with the Bandits and Endless Security Challenges in Katsina State, Nigeria (2019-2020) - Muhammad Abdullahi Maigari; Umar Dantani; Ibrahim Arafat (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2021)
The activities of criminals have been on the rise and the security situation deteriorated after negotiations between the State Government and the criminals in Nigeria. This paper assesses the context of armed banditry, cattle rustling, and kidnappings in Katsina State. The researchers adopted a cross-sectional study design and explanatory research type. A field survey was conducted in Batsari town and two villages: Zamfarawa and Bakiyawa. In-Depth Interviews (IDI) were conducted with some residents of the villages and some armed bandits. A non-probability sampling and snowballing technique were adopted to sample the research participants for the interviews. The study found that the Katsina State Government has not understand fully the security challenge and hence identified the wrong leaders of the criminals for negotiation, this is because there are three categories of criminals in the areas. This incensed some of the groups of criminals to intensify their attacks, kidnapping, and the rustling of livestock.